Rhythm is my beat : jazz guitar great Freddie Green and the Count Basie sound - Green, Alfred, 1938- (Studies in jazz, 2015)
In Rhythm Is My Beat: Jazz Guitar Great Freddie Green and the Count Basie Sound, Alfred Green tells the story of his father, rhythm guitarist Freddie Green, whose guitar work served as the pulse of the Count Basie Band.